ANALISIS PENGARUH METODE DISKUSI KELOMPOK TERHADAP KEMAMPUAN PENGEMBANGAN IDE DALAM PENULISAN KARYA ILMIAH MAHASISWA - Mara Untung Ritonga; Agnesya Joy Simanungkalit; Helena Sitinjak; Jupeni Silaban; Muhammad Andra Febrian Siregar; Rifcha Trialya Manurung; Santri Yani Br Ginting (STKIP Subang, 2026)
This study aims to analyze the effect of implementing group discussion methods on students' ability to develop ideas in scientific writing. The research is motivated by the persistent academic shock experienced by first semester students, who often struggle with topic novelty, argument construction, and the use of relevant references. A quantitative descriptive approach using a survey method was employed. The sample consisted of 40 first-semester students of the Chemistry Education Study Program at Universitas Negeri Medan, selected through purposive sampling. Data were collected using a 1–5 Likert scale questionnaire distributed via Google Form. Data analysis used descriptive statistics (percentages) and inferential statistics (Simple Linear Regression, t-test, and Coefficient of Determination R²) with SPSS. The results show that the implementation of group discussion is in the very high category (85.0%), with academic anxiety reduction as the highest indicator (86.4%). Students' idea development ability is in the high category (81.0%). The regression equation Y = 12.45 + 0.72X with a t-value of 5.84 (Sig. 0.000 < 0.05) indicates a positive and significant influence. The R² value of 0.473 reveals that group discussion contributes 47.3% to the improvement of students' idea development ability. These findings reinforce Vygotsky's social constructivism theory and confirm that structured group discussion is an effective strategy to overcome academic shock among first-semester students.